PERSPEKTIF GEOGRAFI DALAM MEMAHAMI KONTEKS PERUBAHAN IKLIM - Andri Noor Ardiansyah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Climate change is happening today is a necessity that we should not ignore. No other indicator is the increasing temperature of the Earth from 1860 until today, and rising sea levels. The main trigger is the increasing concentration of green house effect (GHE) emissions, particularly carbon dioxide (CO2) in the atmosphere. This is caused by the increasing human activity as well, such as industrial activities, the use of motor vehicles, and rampant illegal logging. If left unchecked it will have an impact in the form of threats to human life in all areas. Therefore we need a comprehensive knowledge in studying the phenomenon of climate change systematically. Such knowledge is nothing else can be obtained through a given geography learning in educational institutions. Geography provides a way to analyze the phenomenon by using three approaches, namely; approach to spatial, ecological, and complex region. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1351